2015
DOI: 10.1590/s1806-37132015000004409
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the perception of dyspnea in healthy subjects assessed through inspiratory resistive loading

Abstract: Objective: Few studies have evaluated the variability of the perception of dyspnea in healthy subjects. The objective of this study was to evaluate the variability of the perception of dyspnea in healthy subjects during breathing against increasing inspiratory resistive loads, as well as to assess the association between the level of perception of dyspnea and the level of physical activity. Methods: This was a cross-sectional study involving healthy individuals 16 years of age or older. Subjects underwent insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
8
2
Order By: Relevance
“…We observed slow gait speed and consequently low distance walked on the SMWT. Comparing our SMWT results with those observed in healthy individuals by Ziegler et al 18 and Burr et al, 19 we found lower distances walked. Pataky et al 6 reported that obese women tend to have slower gait speeds and accompanying shorter stride lengths, relatively less powerful lower limbs and a poorer endurance compared to lean individuals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed slow gait speed and consequently low distance walked on the SMWT. Comparing our SMWT results with those observed in healthy individuals by Ziegler et al 18 and Burr et al, 19 we found lower distances walked. Pataky et al 6 reported that obese women tend to have slower gait speeds and accompanying shorter stride lengths, relatively less powerful lower limbs and a poorer endurance compared to lean individuals.…”
Section: Discussionsupporting
confidence: 82%
“…22 Regarding the Borg scale, this study has shown a significant perception of exertion among our obese population studied. Ziegler et al 18 had observed lower values for this score among healthy individuals, with only 23.8% of the individuals achieving a score above 5 points; compared with the mean score of 12.9 in this study, it is reasonable to conclude that obesity has a significant impact on the perception of breathlessness. A meta-analysis that considered moderating variables such as sex, fitness level, psychological status, and mode of exercise showed that, although the validity of the scale of perceived exertion was not as high as originally reported, the relationships with physiological measures of exercise intensity remained high.…”
Section: Discussioncontrasting
confidence: 46%
“…Individuals presenting with excessive breathlessness may be truly deconditioned, as in the case of a post-critical illness patient, or have a perception that their breathlessness with exercise is abnormal despite normal physiological responses to skeletal and respiratory effort during cardio­pulmonary exercise testing (CPET) [ 1 , 2 ]. Perceived breathlessness for any given task or activity can vary widely between individuals with no association found between the level of perception of ­dyspnoea and the level of physical activity [ 13 ]. The athlete with EID may report excessive breathlessness due to a hypersensitivity to their normal physiological response.…”
Section: Deconditioning and The Physiological Limitmentioning
confidence: 99%
“…Dyspnea can be described by the patient as a subjective experience of respiratory discomfort, shortness of breath, or difficult breathing (15) . Furthermore, it can be evaluated objectively by the nurse for the identification of signs of respiratory discomfort causing changes in the normal respiratory pattern (9) . Regarding the accuracy measures, dyspnea had a high sensitivity in the present investigation, which diverges from another study in which this characteristic did not present a relevant percentage (5) .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the characteristic dyspnea was evaluated differently from the conceptual definitions of other studies that define it as a subjective experience of respiratory discomfort, being considered qualitatively distinct with variable intensity (9) . Considering that the quantification of a subjective sensation such as "shortness of breath" is extremely difficult, especially in the pediatric population, in this study, we chose to evaluate dyspnea from the identification of signs of respiratory discomfort, such as nasal flaring and suprasternal, supraclavicular, subcostal, intercostal, and sternal abnormal chest retraction.…”
Section: Methodsmentioning
confidence: 99%